Structural characterization and prebiotic potential of polysaccharides from Polygonatum sibiricum - Zihan Qi; Tiexiang Gao; Jingjing Li; Shuhan Zhou; Zhigang Zhang; Mingzhu Yin; Haiming Hu; Hongtao Liu (Food Science and Human Wellness)
Polygonatum sibiricum has been widely used due to its excellent biological activities. We prepared a novel polysaccharide from P. sibiricum (PSP) in this study. According a monosaccharide composition analysis, PSP was mainly composed of fructose and glucose with a molar percentage of 93.81:5.12. The main linkage types were identified as α-D-Glcp-1→ and →2-β-D-Fruf-1→. The molecular weight of PSP showed no significant change after simulated salivary and gastrointestinal digestion. However, PSP could be broken down by intestinal bacteria. Our findings revealed that PSP administration increased the abundance of probiotics such as Bifi dobacterium. Furthermore, the results showed that gut microbes could utilize PSP to produce short-chain fatty acids including acetic acid, propionic acid, and butyric acid. Also, the PSP fermentation broth displayed an excellent scavenging effect on free radicals, including 2, 2-diphenyl-1-picrylhydrazyl radical, superoxide radical, and hydroxyl radical. In summary, this study will help to promote the application of PSP as prebiotics in functional food and the medical industry.